Geographical Educational Path: A new geospatial approach - Jażdżewska, Iwona; Babuca, Dominika (Bulletin of Geography. Socio-economic Series, 2022)
The mobility of young people during their education has a spatial pattern. This paper presents a new proposal to study the geographical educational path of people. Its elements are points (addresses of schools) and lines connecting successive schools of each of the researched persons. The results can be useful for detecting patterns of educational pathways in different countries, social groups, and comparing them. Indirectly, they can be used to study mobility, gentrification processes in academic cities, and to indicate the range of schools studied. The study was carried out among a group of students at the University of Lodz. Visualisation and analysis of their geographical educational path showed that most of them attended schools near their place of residence, which indicates their low mobility during their studies. Surprisingly, there was a lack of mobility when entering a master’s degree program. The results showed low mobility of students and indirectly of their families during the education period. The all research process would be carried out using Geographical Information System (GIS) tools.